2009
DOI: 10.1128/iai.01070-08
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of SOCS3 in Regulation of CD11c + Dendritic Cell-Derived Osteoclastogenesis and Severe Alveolar Bone Loss

Abstract: To investigate the role of suppressor of cytokine signaling (SOCS) molecules in periodontal immunity and RANKL-mediated dendritic cell (DC)-associated osteoclastogenesis, we analyzed SOCS expression profiles in CD4؉ T cells and the effect of SOCS3 expression in CD11c ؉ DCs during periodontal inflammation-induced osteoclastogenesis and bone loss in nonobese diabetic (NOD) versus humanized NOD/SCID mice. Our results of ex vivo and in vitro analyses showed that (i) there is significantly higher SOCS3 expression a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 63 publications
(184 reference statements)
2
36
0
Order By: Relevance
“…Zhang et al demonstrated that a higher SOCS3 expression level is associated with RANKL-mediated alveolar bone loss and enhances CD11c + DC-derived osteoclastogenesis in vivo and in vitro. The reduced expression of functional SOCS3 in CD11c + DCs results in significantly lower osteoclastogenesis and dendritic cell-derived osteoclasts development during immune interactions with T cells, based on TRAP expression and bone resorptive activity (42). In SOCS3-deficient bone marrow-derived monocytes, the expression levels of TNF-receptor-associated factor-6 and IκB are drastically reduced.…”
Section: Discussionmentioning
confidence: 94%
“…Zhang et al demonstrated that a higher SOCS3 expression level is associated with RANKL-mediated alveolar bone loss and enhances CD11c + DC-derived osteoclastogenesis in vivo and in vitro. The reduced expression of functional SOCS3 in CD11c + DCs results in significantly lower osteoclastogenesis and dendritic cell-derived osteoclasts development during immune interactions with T cells, based on TRAP expression and bone resorptive activity (42). In SOCS3-deficient bone marrow-derived monocytes, the expression levels of TNF-receptor-associated factor-6 and IκB are drastically reduced.…”
Section: Discussionmentioning
confidence: 94%
“…(32) by a large number of cytokines and systemic hormones. (36)(37)(38)(39)(40)(41)(42) Microarray analysis of bones of Terc À/À mice provided evidence that the bone microenvironment contains high levels of several proinflammatory factors known to affect osteoclast generation and bone resorption (eg, interleukin 1b and tumor necrosis factor a). Interestingly, RANKL was upregulated (1.1-fold) and OPG was downregulated (1.4-fold), suggesting increased RANKL/ OPG (2-fold).…”
Section: Discussionmentioning
confidence: 99%
“…The soft magnetic material Co 90 Fe 10 is chosen as the discontinuous metal layers for its high spin polarization. 10 Magnetic and transport properties of these organic/CoFe discontinuous multilayers are studied as a function of CoFe layer thickness. plane anisotropy.…”
Section: Thickness Dependence Of Magnetic and Transport Properties Inmentioning
confidence: 99%